The incomprehensibility of God: Reciprocal interdependence between mystery and knowledge - Dirk G. Van der Merwe (Verbum et Ecclesia)
This research investigates the theological concept, ‘The incomprehensibility of God’, from a Johannine perspective. The primary objective is to discern the ‘incomprehensibility of God’ from a reciprocal interdependence between knowledge (understanding) and mystery. It explains how the endeavour to understand the divine, continuously prompts mystery. Humans can only know, communicate with, relate to and talk about God, in terms of human perspectives and conventions within the human idiom. Therefore, the modus operandi starts with an articulation of how this dualism (knowledge versus mystery) relates and should be interpreted. This is followed by a discourse analysis of the Johannine prologue to point out various semantic networks to facilitate dualistic reasoning in this research. Thereafter, the incomprehensibility of God is discerned from the following four perspectives: the ‘identity’, ‘articulation’, ‘activities’ and ‘involvement’ of God in God’s creation as formulated according to the Prologue of the Gospel of John. Finally, the investigation of and contemplation on the incomprehensibility of God becoming a spiritual, cognitive and discerning never-ending event.